ASUHAN KEBIDANAN KEHAMILAN DI PRAKTIK MANDIRI BIDAN ROSLINA KECAMATAN SAMUDERA KABUPATEN ACEH UTARA - Yani, Sukma; Rosyita (JURNAL KESEHATAN ALMUSLIM, 2023)
The maternal mortality rate in Indonesia is currently still far from the target, in line with the Sustainable Development Goals (SDGs) of 70 per 100,000 live births in 2030. The Maternal Mortality Rate is an indicator to see the health status of women and is a component of the development index and the quality of life index. The purpose of this care is to provide midwifery care at Roslina Midwife Independent Practice, Samudera District, North Aceh Regency according to obstetric pregnancy service standards using varney midwifery management and documented using the SOAP method. Type of report in the form of a case study, carried out at PMB Roslina, Samudera District, North Aceh Regency from December 2021 to January 8, 2022, Subject is Mrs. S, 21` years old with G1P0A0, HPHT dated 08-06-2021, TTP dated 15-03-22, Pregnancy care that has been carried out on Mrs. S visited 3 times, namely visit 1 on 25 December 2021, visit II on 31 December 2021, and visit III on 08 January 2022, All care provided is in accordance with the standards provided. It is hoped that patients will always have awareness of the importance of health during pregnancy to prevent maternal and infant mortality.